NON-NATIVE PRONUNCIATIONS OF ENGLISH - Mukhiddinova (Abdullayeva) Dilafruz Mansurovna (International Journal on Integrated Education, 2023)
This article focuses on the Non-native pronunciations of English result from the common linguistic phenomenon in which non-native speakers of any language tend to transfer the intonation, phonological processes and pronunciation rules of their first language into their English speech. They may also create innovative pronunciations not found in the speaker's native language.